Restoration of love / Sharkawi Che Din - Che Din, Sharkawi (Faculty of Art and Design, 2021)
My work frequently focuses on nature and human interest, seamlessly blending with the art and design's principle. My style is vibrant, eye-catching, engaging with photographic resources that are adjacent to the audience. The subject that captivates me is things that exist around us. In nature, we could find the rhythm of life. Nature inspires me to be grateful and kind to my surroundings. This pursuit is crucial as it contributes to sustaining the ecosystem's rehabilitation and safeguarding our biodiversity for the future generation to experience the majesty of our surroundings.